Lucky Chill Cafe Logo Design Using Roland Barthes’ Visual Semiotics for Brand Image - Putu Gede Maha Vivaldi Pradnyana; I Gede Wirya Mahendra Nandanawana Putra (fakultas Desain Komunikasi Visual, 2026)
Logo design constitutes a critical stage in establishing a brand’s visual identity, as it functions as a sign system that communicates brand values and character. This study aims to design the Lucky Chill Cafe logo using Roland Barthes’ visual semiology approach to build a brand image representing the relaxed lifestyle and togetherness of urban youth. A descriptive qualitative method was employed using Wheeler’s visual identity design model, consisting of conduct research, design identity, and implement and manage, integrated with Barthes’ semiotic analysis of denotation, connotation, and myth. Data were collected through semi-structured interviews with the cafe owner and manager, non-participant observation, and visual documentation. The resulting logo features an oval composition containing seven visual elements: the sun, waves, palm trees, cutlery, a coffee cup, the shaka hand gesture, and rounded typography. These elements represent a tropical atmosphere and culinary activity, convey friendliness and casualness, and construct a narrative of a laid-back urban youth lifestyle. The study contributes to the development of a meaning-driven logo design methodology by positioning Barthes’ semiology as a generative framework in the ideation process rather than solely as a post-design analytical tool.